Dual Superconformal Symmetry of the ABJM Theory - Lipstein, A (2011)
We summarize the proof that all tree-level amplitudes of the ABJM theory enjoy dual superconformal symmetry. This note is based on arXiv:1008.0041 [hep-th] and arXiv:1012.5032 [hep-th]. © 2011 Elsevier B.V.